Relationship between Stationary and Mobile Phase Composition and its Influence on the Retention Time of Some Analytes in Gas Chromatography - R. Nasuto (Adsorption Science & Technology)
A binary methanol vapour/hydrogen gas mixture has been used as the mobile phase in gas chromatography. Through the use of modified frontal analysis (undertaken just before measurements of the retention of the tested analytes), it has been possible to determine the adsorption isotherm of the mobile phase modifier (methanol) under typical conditions for a chromatographic process. It was found that adsorption of the mobile phase modifier on the column packing surface caused a decrease in the retention times of all the analytes tested. Furthermore, as a result of such adsorption, an increase in the degree of hydrophobization of the column packing surface also occurred, leading to a decrease of the selectivity of the packing.